INVESTIGATION OF THE PROPERTIES OF FOAM GENERATORS - Turapov Farkhod Khursanovich (American Journals Publishing, 2023)
Is to research the development and properties of foam concrete using local raw materials.
Keywords: Foam concrete, technology, parameter, foaming agent, stability.